Inverse response of 231Pa/230Th to variations of the Atlantic meridional overturning circulation in the North Atlantic intermediate water - Süfke, Finn; Schulz, Hartmut; Scheen, Jeemijn; Szidat, Sönke; Regelous, Marcel; Blaser, Patrick; Pöppelmeier, Frerk; Goepfert, Tyler J.; Stocker, Thomas F.; Lippold, Jörg (Geo-marine letters, 2020)
This study aims to provide a more detailed understanding of the behavior of 231Pa/230Th under varying ocean circulation regimes. The North Atlantic provides a unique sedimentary setting with its ice-rafted detritus (IRD) layers deposited during glacial times. These layers have been found north of 40° N (Ruddiman Belt) and are most pronounced during Heinrich Stadials. Most of these sediments have been recovered from the deep North Atlantic basin typically below 3000 m water depth. This study reports sedimentological and sediment geochemical data from one of the few sites at intermediate depth of the open North Atlantic (core SU90-I02, 45° N 39° W, 1965 m water depth) within the Ruddiman Belt. The time periods of Heinrich Stadials 1 and 2 of this core were identified with the help of the major element composition by XRF scanning and by IRD counting. Along the core profile, the sedimentary 231Pa/230Th activity ratio has been measured as a kinematic proxy for the circulation strength. The 231Pa/230Th record shows highest values during the Holocene and Last Glacial Maximum, above the natural production ratio of these isotopes. During Heinrich Stadials 1 and 2, when Atlantic meridional overturning circulation was most reduced, the 231Pa/230Th record shows overall lowest values below the production ratio. This behavior is contrary to classical findings of 231Pa/230Th from the northwestern Atlantic where a strong Holocene circulation is associated with low values. However, this behavior at the presented location is in agreement with results from simulations of the 231Pa/230Th-enabled Bern3D Earth system model.
Im Titel sind "231" und "230" als Hochzahlen dargestellt
Gesehen am 26.10.2020